Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/opo.12834
|View full text |Cite
|
Sign up to set email alerts
|

One‐year results of the Variation of Orthokeratology Lens Treatment Zone (VOLTZ) Study: a prospective randomised clinical trial

Abstract: Purpose: To present the 1-year results of the Variation of Orthokeratology Lens Treatment Zone (VOLTZ) Study, which aims to investigate the myopia control effect of orthokeratology (ortho-k) lenses with different back optic zone diameters (BOZD). Method: Children, aged 6 to <11 years, having myopia −4.00 D to −0.75 D, were randomly assigned to wear ortho-k lenses with 6 mm (6-MM group) or 5 mm (5-MM group) BOZD. Data collection included changes in refraction, vision, lens performance and binding, ocular health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
60
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 46 publications
9
60
1
Order By: Relevance
“…Despite its retrospective design in nature, this was the first study directly investigating the relationship between orthokeratology lens design (especially back optical zone diameter) and myopia control efficacy in children and juveniles, which opened a possibility of optimizing orthokeratology lens designs for better myopia control efficacy. Recently, Guo et al 25 also reported that children wearing orthokeratology lenses with smaller (5.0 mm) back optical zone diameter had significantly slower annual axial elongation (0.04 ± 0.15 mm) as compared with those wearing larger (6.0 mm) back optical zone diameter (0.17 ± 0.13 mm), resulting in a retardation effect of 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its retrospective design in nature, this was the first study directly investigating the relationship between orthokeratology lens design (especially back optical zone diameter) and myopia control efficacy in children and juveniles, which opened a possibility of optimizing orthokeratology lens designs for better myopia control efficacy. Recently, Guo et al 25 also reported that children wearing orthokeratology lenses with smaller (5.0 mm) back optical zone diameter had significantly slower annual axial elongation (0.04 ± 0.15 mm) as compared with those wearing larger (6.0 mm) back optical zone diameter (0.17 ± 0.13 mm), resulting in a retardation effect of 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A short-term study of different compression factors found that no significant changes in eye parameters were found between the different design lenses [ 28 ]. However, OK lens of smaller back optic zone diameter achieved better curative effect [ 29 , 30 ]. Further investigations will be need to make OK lens more effective in myopia control.…”
Section: Discussionmentioning
confidence: 99%
“…One such design modification is focused on reducing the central treatment zone diameter created on the cornea. [41][42][43] With children being the target population for myopia management using OrthoK, safety is an ever-present concern. Regular and careful follow-up care for OrthoK patients is critical to ensure ongoing corneal health and maintenance of clean lenses.…”
Section: Discussionmentioning
confidence: 99%
“…One such design modification is focused on reducing the central treatment zone diameter created on the cornea. 41–43…”
Section: Discussionmentioning
confidence: 99%